Social wasp diversity (Vespidae, Polistinae) in a forest fragment in the northeast of são paulo state sampled with different methodologies - Lima, Alexandre C. O.; Castilho-Noll, Maria Stela M. [UNESP]; Gomes, Bruno [UNESP]; Noll, Fernando B. [UNESP] (My University, 2010)
Social wasp diversity in Semideciduous Seasonal Forests of the northeast of São Paulo State is poorly known, causing a lack of information on the diversity of these wasps from these areas which have been degraded. The objective of this work was to evaluate the social wasp (Vespidae, Polistinae) diversity in a Semideciduous Seasonal Forest of the northeast of São Paulo State and to compare three different kinds of sampling methodology. Surveys were conducted from August 2005 to September 2006 in the interior, edge and matrix of a Semideciduous Seasonal Forest fragment in Patrocínio Paulista city, São Paulo State. Three methodologies were used : 1. Active collection in flowers, 2. Searching for nests, 3. Active collection with attractive liquid. Thirty species of social wasps were collected in the fragment, but the diversity was highest in the edge. Active collection with attractive liquid was the most efficient methodology. Despite the high levels of deforestation, forest fragments in São Paulo State have a high diversity of social wasps, reinforcing the importance of their preservation.
Keywords: Entomology; Forest fragments; Hymenoptera; Sampling methods; Social insects